Output feedback tracking control of MIMO systems using a fuzzy disturbance observer and its application to the speed control of a PM synchronous motor. - Euntai Kim (IEEE Transactions on fuzzy systems)
One of the most important objectives in the design of control systems is to achieve the good tracking performance in the presence of the internal parameter uncertainty and external disturbance. In this paper, a new multiple-input-multiple-output (MIMO) fuzzy disturbance observer (FDO) based on output measurement is developed to achieve the goal. A filtered signal is introduced to resolve the algebraic loop encountered in the conventional FDO. The contribution of the disturbance observation error ζ to updating the parameters of the fuzzy system is analyzed in the sense of L2 and L∞. Then, the MIMO FDO is modified and the high gain observer (HGO) is employed to implement the output tracking control system. It is shown in a rigorous manner that the disturbance observation error, the tracking error and the state observation error converge to a compact set of which size can be kept arbitrarily small. Finally, the suggested method is applied to the speed control of a permanent magnet synchronous motor (PMSM) in the presence of the internal parameter uncertainty and external disturbance. The effectiveness and the feasibility of the suggested method are demonstrated by computer simulation.